Germanic diminutives: a case study of a gap in Norwegian - Alexiadou, Artemis; Lohndal, Terje (The journal of comparative Germanic linguistics, 2023)
It is well known that German and Dutch have productive diminutive morphology. What is much less discussed is the fact that several other Germanic languages do not have such productive morphology, notably the Scandinavian languages. Instead, these languages form compounds to express a diminutive meaning. This paper addresses the puzzle of why the Scandinavian languages do not have productive diminutive morphology. The paper argues that the culprit is the particular definite suffix that the Scandinavian languages have. This is a postnominal definite suffix that occupies a low position in the nominal functional spine. It is argued that the presence of this suffixed article accounts for the lack of productive synthetic diminutive formation in these languages.